2020
DOI: 10.1029/2020jc016134
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the South Pacific Western Subtropical Mode Water and Its Relationship With ENSO During the Argo Period

Abstract: This study investigates variability of the South Pacific western subtropical mode water (SPWSTMW), its physical processes, and relationship with El Niño‐Southern Oscillation (ENSO), using a gridded Argo data product from January 2004 to September 2019. On seasonal timescale, the SPWSTMW volume shows a significant variability, which involves three periods: the formation period (June–October), the isolation period (November–February), and the dissipation period (March–May). This seasonal variability is related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…A recent study (59) analyzing 30-year ocean reanalysis data showed that the North Pacific STMW subducted and advected southward from the formation region south of the KE also controlled the overlying stratification through the uplifting effect on decadal timescales. STMWs in other basins also show interannual to decadal variations (60)(61)(62). In addition, the North Atlantic STMW has exhibited a notable decline in recent years (63), which might have increased upper-ocean heat content and hurricane intensity (64).…”
Section: Discussionmentioning
confidence: 98%
“…A recent study (59) analyzing 30-year ocean reanalysis data showed that the North Pacific STMW subducted and advected southward from the formation region south of the KE also controlled the overlying stratification through the uplifting effect on decadal timescales. STMWs in other basins also show interannual to decadal variations (60)(61)(62). In addition, the North Atlantic STMW has exhibited a notable decline in recent years (63), which might have increased upper-ocean heat content and hurricane intensity (64).…”
Section: Discussionmentioning
confidence: 98%
“…3 and 7 ). For instance, in the Subtropical Mode Water layer, we separately define regional Subtropical Mode Waters at the subtropical South Atlantic 26 , 47 , 78 , 79 (SA-STMW), North Atlantic 26 , 47 , 80 82 (NA-STMW, also known as the North Atlantic’s Eighteen Degree Water), western South Pacific 26 , 47 , 83 , 84 (SP-WSTMW), eastern South Pacific 26 , 47 , 85 (SP-ESTMW), western North Pacific 26 , 47 , 86 88 (NP-STMW), eastern North Pacific 26 , 47 , 86 , 88 (NP-ESTMW), and Indian Ocean 26 , 47 , 89 , 90 (IO-STMW), by further using a set of more specific density and geographic limit (Figs. 3 , 7 , and 8b, e ).…”
Section: Methodsmentioning
confidence: 99%
“…Ocean temperature, one of the most important variables of seawater, plays a significant role in marine disasters, marine ecosystems, ocean dynamics, and climate changes [1,2], for example, it is closely related to the formation of many high impact thermos-dynamical ocean-atmospheric processes, such as the marine heatwaves [3,4], thermocline layer formation [5], El Niño evolution [6,7], or deep-water formation [8,9]. To better understand the role of ocean temperature in marine disaster and ecosystems, ocean circulation and climate changes, it is essential to identify the ocean subsurface thermal structure (OSTS) accurately.…”
Section: Introductionmentioning
confidence: 99%